Case report: Ovarian mucinous tumor with a mural nodule of liposarcoma: a rare case - Li, Jiezhen; Huang, Haijian; Zeng, Qiang; Chen, Xin; Chen, Lingfeng (Frontiers in Oncology, 2024)
Background Ovarian mucinous tumor with a mural nodule is a rare and special type of ovarian surface epithelial–stromal tumor. Mural nodules are morphologically classified into three types: sarcoma-like, anaplastic carcinomatous, and true sarcomatous nodules. Ovarian mucinous tumors with true sarcomatous mural nodules are rare and challenging to diagnose, with only 10 cases reported worldwide. Currently, liposarcoma mural nodules remain unreported. Case presentation A 91-year-old woman was hospitalized for postmenopausal vaginal bleeding for 3 weeks. Imaging revealed a large cystic mass (20.0 cm × 17.7 cm × 12.8 cm) on the right ovary. The mass was multilocular cystic, with a mural nodule (1.4 cm × 1.2 cm × 1.0 cm) in the focal cyst wall. Based on histological morphology, immunohistochemical staining, and MDM2/CDK4 fluorescence in situ hybridization testing, the diagnosis was ovarian mucinous cystadenoma with a mural nodule of well-differentiated liposarcoma. To the best of our knowledge, this has never been reported before. High-throughput sequencing identified KRAS mutations in the ovarian mucinous cystadenoma. However, the liposarcoma mural nodule did not exhibit KRAS mutations but displayed copy number amplifications of CDK4 and DDR2, as well as a frameshift mutation in exon 13 of ASXL1 (p. A627Gfs*8). Conclusions This case broadens the morphological spectrum of mural nodules in ovarian mucinous tumors, deepening our knowledge of this rare morphology. Meanwhile, through high-throughput sequencing, we found no overlapping genetic evidence between the liposarcoma mural nodule and associated ovarian mucinous cystadenoma.